The Influence of Oral Hygiene Behavior on Periodontal Disease Status of Fishpond Community in District Sidoarjo - Narita Ajeng Loviana; Melok Aris Wahyukundari; Ristya Widi Endah Yani; Peni Pudjiastuti; Hestieyonini Hadnyanawati; Sri Lestari; I Dewa Ayu Ratna Dewanti (Humanistic Network for Science and Technology (HNST), 2018)
Background: Periodontal disease is one of the most common oral diseases in Indonesia. Poor oral hygiene behavior has been seen as a risk factor for periodontal disease. Oral hyigiene behavior is different in each individual or group, as well as the fishpond community. Purpose: To analyze the influence of oral hygiene behavior on periodontal disease status of fishpond community. Methods: This study was a observational analytic study with cross sectional approach. The samples were fishpond community in Banjar Kemuning village, district Sidoarjo which amounts 100 people in age range between 26 to 65 years old. Oral hygiene behavior in the form of knowledges and attitudes were measured using a closed questionnaire and oral hygiene behavior in the form of practices were measured using a checklist questionnaire, while Periodontal Disease Index (PDI) was used to measured periodontal disease status. Results: Ordinal regression analysis of the oral hygiene behavior on periodontal disease status showed significant value that was 0,043. Conclusion: Oral hygiene behavior has influence on periodontal disease status of fishpond community in District Sidoarjo. Keywords: Oral hygiene behavior, Knowledge, Attitude, Practice, Periodontal disease status, Fishpond